Designing and implication of pictograms in Universities of Tehran (IRAN) - Keshavarzi, Firouzeh; Mohd Adnana, Hamedi (2017)
Pictograms have many implications nowadays and are used for simple and fluent pictorial interpretations.These concepts are usually informative, conductive and warning. These kinds of icons are used in order to simplify the communication in an environment as are used in airports, terminals, railroad stations, parks, zoo, hospitals, drug stores and so on.To provide an efficient contrast, pictograms are often in black and white.Nowadays in different public places and landscape design pictograms are used for perfect communication.By the ways these icons are related to the civilization and tribal culture.Designing pictograms need a permanent search for better plan for better information transfer.In this project researcher designed and executed pictograms for better conduction in some selected Universities in Iran at 2015. The project was done for internal and external places of selected universities.Absence of informative and pictorial icons in universities environments causes wandering about for novices and they are not able to find different places like libraries, restaurant, and offices and so on.This study resulted in better communication in campus environments.Researche hope pictograms will find their real and proper role in Iranian art area.